Clogging of saturated porous media by silt‐sized suspended solids under varying physical conditions during managed aquifer recharge. Issue 14 (20th June 2018) - Du, Xinqiang; Ye, Xueyan; Zhang, Xiaowan
Abstract: Managed aquifer recharge is an effective method for utilizing excess flood flows, but clogging of porous media is a limiting factor in the implementation of this water storage technique. In recent years, much research on the physical clogging of porous media during artificial recharge has been conducted. However, the understanding of clogging due to silt‐sized suspended solids (SS) is still inadequate, especially under varying physical conditions. Here, we subjected sand columns to controlled rates of flow and SS suspensions to investigate the influence of media size, SS size, SS concentration, and flow velocity on the clogging of porous media by silt‐sized SS. The results show that the diameter ratio of SS particles to sand grains is the dominant factor influencing the position of physical clogging. As pore velocity increased, the mobility of silt‐sized SS was enhanced and retention in the porous media decreased noticeably. The spatial retention profiles in the porous media were found to vary greatly at different flow velocities. The SS concentration of the infiltrating suspension also dramatically influenced the mobility and deposition of silt‐sized SS particles, such that high concentrations accelerated the clogging process. As the different physical factors changed, the breakthrough curves and retention profiles of silt‐sized SS particles changed obviously and the mechanisms of retention differed. On the whole, clogging position is mainly determined by particle size ratio, but clogging rate is dominated by a variety of factors including particle size ratio, SS concentration, and flow velocity.